Justification of the Subject of Cognition Problem in Modern Social and Legal Sciences Methodology - DUDCHENKO, Valentina V.; TSURKAN-SAIFULINA, Yuliia V.; VITMAN, Konstiantyn M. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The article is devoted to the study of the essential characteristics of the subject of cognition. The process of cognition, being one of the oldest issues in the history of humankind, has always been and remains highly relevant today. This is due to the irrepressible desire of a person to know the world around her/him and herself/himself. If the study of the surrounding world is basically the prerogative of the natural sciences, then self-cognition is the object of study in the humanities. The process of cognitive activity is considered by a number of the humanities and social sciences: philosophy (in a generalized sense), history, psychology, pedagogy, sociology, etc., but it begins to occupy a separate place in the philosophy of law. Modern human needs to know the measure, opportunity, freedom and responsibility of the process of cognition. In the article, from the point of view of critical realism, the current state of the methodology of cognition is analyzed and the necessary tendencies in changing the worldview and defining the new methodology of the humanities are substantiated. The experience of the post-Soviet countries with dogmatic ideology and destructive methodology was used as an illustrative material. It has been established that only a free-thinking subject and a methodology developed on the principles of the supremacy of spiritual values can improve the reverent approach to the person and the world as a whole and come closer to the cognition of absolute truth.